Pemahaman Guru Pembimbing Tentang Kepribadian Siswa Asuh di SMAN 2 Rejang Lebong - Imam Rifai; Miftahul Rahmah; Ifnaldi; Edi Wahyudi (STKIP Subang, 2026)
Guidance counselors play a vital role in the implementation of guidance and counseling programs in schools and are responsible for shaping students' personalities. They help develop students' personalities through counseling sessions and by utilizing opportunities outside of formal counseling hours. This study is a library research aimed at investigating, analyzing, and synthesizing previous research conducted within this field of study. It involves the collection and evaluation of various journal articles, books, research reports, and other relevant sources related to the topic. Students' personalities vary; some are extroverted while others are introverted. More specifically, students exhibit diverse personality types such as sanguine, melancholic, phlegmatic, and choleric. The study also explores guidance counselors’ understanding of these personality types. Sanguine students are enthusiastic and cheerful in learning, yet may act impulsively based on emotions. Phlegmatic students are self-controlled, observant, and critical, but may also be self-centered. Melancholic students tend to be sensitive and emotionally deep. Choleric students are disciplined and responsible but may lack emotional expression. Assertive students are characterized by being firm, opinionated, and critical thinkers.